The Critical Roles of Proteostasis and Endoplasmic Reticulum Stress in Atrial Fibrillation - Sirish, Padmini; Diloretto, Daphne A.; Thai, Phung N.; Chiamvimonvat, Nipavan (Frontiers in Physiology, 2022)
Atrial fibrillation (AF) remains the most common arrhythmia seen clinically. The incidence of AF is increasing due to the aging population. AF is associated with a significant increase in morbidity and mortality, yet current treatment paradigms have proven largely inadequate. Therefore, there is an urgent need to develop new effective therapeutic strategies for AF. The endoplasmic reticulum (ER) in the heart plays critical roles in the regulation of excitation-contraction coupling and cardiac function. Perturbation in the ER homeostasis due to intrinsic and extrinsic factors, such as inflammation, oxidative stress, and ischemia, leads to ER stress that has been linked to multiple conditions including diabetes mellitus, neurodegeneration, cancer, heart disease, and cardiac arrhythmias. Recent studies have documented the critical roles of ER stress in the pathophysiological basis of AF. Using an animal model of chronic pressure overload, we demonstrate a significant increase in ER stress in atrial tissues. Moreover, we demonstrate that treatment with a small molecule inhibitor to inhibit the soluble epoxide hydrolase enzyme in the arachidonic acid metabolism significantly reduces ER stress as well as atrial electrical and structural remodeling. The current review article will attempt to provide a perspective on our recent understandings and current knowledge gaps on the critical roles of proteostasis and ER stress in AF progression.